The Story of the Second World War - Savage, Katharine (London Oxford University Press, 1957)
The causes of the war and its course from the opening disasters in Europe to final victory. Grades 7-10.
Include Illustration and Index
Keywords: World War (1939-1945) -- The Battle of Norway